The Natural, Social and Economic Conditions and Opportunities for Development of Balmazujvaros, Especially in the Case of the Co-operative Kvaliko - Szabó, Bernadett; Klutsik, Andrea (Acta Agraria Debreceniensis, 2002)
Balmazujvaros as a settlement near Hortobagy has to cope with both advantages and disadvantages. Its natural and social conditions are mainly given, the agricultural characteristic is dominant, and the number of the employed is the highest in the agricultural firms and processing industry. Developing the third sector, including hosting, tourism, eco-tourism, thermal-tourism, may be an opportunity for the city. The subsidy for rural development relating to the SAPARD-programme may contribute to this, as the city is the member of the Association of Hajdu Towns.The agriculture plays an important part in Balmazujvaros in which production and marketing of vegetables and fruits excel. Several farmers realised this opportunity and founded the Marketing Co-operative of Vegetable Producers in Eastern Hungary, that is the Kvaliko. This PO works in a Corporation form and is constantly developing, spreading and expanding its choice making use of the local natural, social and economic conditions and applications for realising its investments. This PO may set an example for the other entrepreneurs and farmers of Balmazujvaros to co-operate and it may be considered as an already realised opportunity.